Refugees' Economic Integration and Firms - Matthew A. Cole; Liza Jabbour; Ceren Ozgen; Hiromi Yumoto (Institute of Labor Economics (IZA), 2024)
We explore whether a civic integration component dedicated to labor market training (the ONA) boosts refugees' economic outcomes and the quality of firms they work for. Using linked employer-employee administrative data from 2014 to 2021 for the Netherlands and Regression Discontinuity design we find that taking the ONA sped up the economic integration of refugees for 3 years in terms of increased employment probability, hours worked and higher hourly wages. We further show that taking the ONA results in refugees working for larger, less labor-intensive and less routine-task intensive firms and experiencing increased job stability. The ONA benefits male and female refugees and particularly those from Syria.
Keywords: J08; J15; 330; refugees; firms; labor market performance; integration exam; Netherlands